Depressive and anxiety symptoms and cortical amyloid deposition among cognitively normal elderly persons: the Mayo Clinic Study of Aging - Krell-Roesch, Janina; Lowe, Val J; Neureiter, Jennifer; Pink, Anna; Roberts, Rosebud O; Mielke, Michelle M; Vemuri, Prashanthi; Stokin, Gorazd B; Christianson, Teresa J; Jack, Clifford R; Knopman, David S; Boeve, Bradley F; et al. (International psychogeriatrics, 2018)
BACKGROUND: Little is known about the association of cortical Aβ with depression and anxiety among cognitively normal (CN) elderly persons. METHODS: We conducted a cross-sectional study derived from the population-based Mayo Clinic Study of Aging in Olmsted County, Minnesota; involving CN persons aged ≥ 60 years that underwent PiB-PET scans and completed Beck Depression Inventory-II (BDI-II) and Beck Anxiety Inventory (BAI). Cognitive diagnosis was made by an expert consensus panel. Participants were classified as having abnormal (≥1.4; PiB+) or normal PiB-PET (<1.4; PiB-) using a global cortical to cerebellar ratio. Multi-variable logistic regression analyses were performed to calculate odds ratios (OR) and 95% confidence intervals (95% CI) after adjusting for age and sex. RESULTS: Of 1,038 CN participants (53.1% males), 379 were PiB+. Each one point symptom increase in the BDI (OR = 1.03; 1.00-1.06) and BAI (OR = 1.04; 1.01-1.08) was associated with increased odds of PiB-PET+. The number of participants with BDI > 13 (clinical depression) was greater in the PiB-PET+ than PiB-PET- group but the difference was not significant (OR = 1.42; 0.83-2.43). Similarly, the number of participants with BAI > 10 (clinical anxiety) was greater in the PiB-PET+ than PiB-PET- group but the difference was not significant (OR = 1.77; 0.97-3.22). CONCLUSIONS: As expected, depression and anxiety levels were low in this community-dwelling sample, which likely reduced our statistical power. However, we observed an informative albeit weak association between increased BDI and BAI scores and elevated cortical amyloid deposition. This observation needs to be tested in a longitudinal cohort study.
Keywords: Fluorodeoxyglucose F18; mozek; Humans; neuropsychologické testy; Longitudinal Studies; lidé středního věku; úzkost; kognice; Female; Aged; fluorodeoxyglukosa F18; stárnutí; Psychiatric Status Rating Scales; senioři; lidé; amyloidní beta-protein; Aging; Anxiety; Neuropsychological Tests; ženské pohlaví; longitudinální studie; psychiatrické posuzovací škály; Amyloid beta-Peptides; Male; Middle Aged; anxiety symptoms; cortical amyloid deposition; Brain; cognitively normal persons; depressive symptoms; Aged, 80 and over; Cross-Sectional Studies; Positron-Emission Tomography; senioři nad 80 let; Depression; mužské pohlaví; Cognition; deprese; pozitronová emisní tomografie; průřezové studie